Chronic rhinosinusitis with nasal polyps: Challenges and prospective - Population-based study - Carvalho, Liliana (2021)
Chronic rhinosinusitis with nasal polyps is a commonly found disease in otolaryngology and its treatment is either medical and/or surgical. This condition is often associated with recurrence, which lead to high morbidity. The retrospective evaluation of the affected population allows the revision of the characteristics of these patients and their disease and identify potential alternative therapies. In this population-based retrospective study, we evaluate 93 patients with the diagnose of Chronic rhinosinusitis with nasal polyps, its main characteristics and symptoms, as well as the therapeutic used and recurrence. According to the results, the treatment is limited and often non-curative, which is evident in certain sub-groups of the population, identified in this study. The recognition of these subgroups and the exploration of new therapeutic targets is of high value for these patients and should be among the future goals of the otolaryngologists.